Religious Education As A Form Of Implementation Of The First Principle Of Pancasila - Apri Winge Adindo; Sutoyo (IJGIE (International Journal of Graduate of Islamic Education), 2026)
Religious education plays a strategic role in instilling the value of Belief in One God as the embodiment of the first principle of Pancasila. However, the development of digital technology poses new challenges to the process of internalising religious values, especially among children. This study aims to analyse the role of the family, community, and educational institutions in implementing the value of Belief in One God in the digital era. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The results of the study show that: (1) children's participation in religious educational institutions is still ongoing, but has undergone changes due to the increasing use of digital technology; (2) the role of society and parents in guiding children against the influence of social media greatly determines children's religious behaviour patterns; (3) the level of formal education of parents is not always directly proportional to the quality of religious education in the family, because busy work schedules often reduce the intensity of interaction with children. Therefore, it is necessary to revitalise religious education based on Pancasila values through collaboration between families, schools, and communities. The implementation of the value of Belief in One God needs to be realised not only through ritual activities but also through role modelling, positive habits, and the use of educational technology relevant to the character of the digital generation. The instilling of these values is an important foundation in shaping the character of Pancasila students who are faithful, devoted to God Almighty, and have noble character.